Construction of gen Z political insights after watching 'Bacapres Bicara Gagasan' on YouTube - Tabitha Hemastuti; Dasrun Hidayat; Zikri Fachrul Nurhadi; Nofha Rina (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2024)
All Indonesians, especially Generation Z, need to be politically literate, as they are the ones who will shape the nation’s future. Since Generation Z constituted the majority of voters in the 2024 election, understanding their political insights is crucial. Despite their digital fluency, many Gen Z individuals remain disengaged from formal political processes. This study aims to analyze how Generation Z constructs political insight after watching the Bacapres Bicara Gagasan program on YouTube. Using a qualitative phenomenological method, this research explores their cognitive, affective, and personal integration experiences. The findings reveal that the program provided new perspectives on politics and influenced how Gen Z evaluates presidential candidates. The study underscores the importance of media, especially YouTube, in enhancing youth political awareness and participation in the digital age.